Experimental results on the retrofitting of hollow brick masonry walls with reinforced high performance mortar coatings. (15th June 2017) - Messali, F.; Metelli, G.; Plizzari, G.
Highlights: A technique for the strengthening of unreinforced hollow brick masonry is presented. A reinforced high-performance mortar coating was connected to the masonry. Six full scale specimens under in-plane loads were tested. Improvements in resistance and displacement capacity of the walls were achieved. The strengthened walls showed a significant delay in cracking formation. Abstract: Many masonry buildings in Europe were built after the Second World War during a booming economy when seismic risk was not properly considered and, as a consequence, seismic codes were not available yet. Several of these buildings are quite small since they are used by one or two families. Because of the huge developments in the knowledge on seismic actions, there is now a major concern for the vulnerability of these buildings under possible earthquakes. The present work focuses on seismic strengthening of a masonry typology widely used for social housing. It is based on hollow masonry bricks with horizontal holes and poor cementitious mortar. Results of quasi-static cyclic tests carried out on full-scale unreinforced masonry walls with different geometries, representing either a shear wall or a pier-spandrel assembly, are presented. The specimens were repaired or strengthened with a thin layer of high-performance mortar reinforced with light steel-mesh. The test results show the effectiveness of the proposed technique since it provides a remarkable enhancement of both lateral strength and displacement capacity.